2019
DOI: 10.1108/pr-07-2018-0277
|View full text |Cite
|
Sign up to set email alerts
|

Modeling team performance from the perspective of politics and ethical leadership

Abstract: Purpose The purpose of this paper is to develop and test a model of team performance by applying social exchange and social capital perspectives in a single model setting. It hypothesizes that team performance is indirectly affected by politics through leader–member capitalization (LMC) and by ethical leadership through leader–member exchange (LMX). Meanwhile, team identification is hypothesized to moderate the relationships between politics and LMC and between ethical leadership and LMX. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 135 publications
(138 reference statements)
1
6
0
Order By: Relevance
“…Thirdly, the results of this study in relation to software development projects align with previous empirical research in that ethical leadership has a positive direct impact on team performance (Lin et al, 2019;Liu et al, 2019;Peng and Lin, 2017;Walumbwa et al, 2012;De Hoogh and Den Hartog, 2008). Moreover, the findings accord with the theory of social exchange proposed by Blau (1964) in that when leaders exhibit ethical behaviours, team members are more likely to reciprocate them and contribute positively to team performance.…”
Section: Theoretical Implicationssupporting
confidence: 87%
See 2 more Smart Citations
“…Thirdly, the results of this study in relation to software development projects align with previous empirical research in that ethical leadership has a positive direct impact on team performance (Lin et al, 2019;Liu et al, 2019;Peng and Lin, 2017;Walumbwa et al, 2012;De Hoogh and Den Hartog, 2008). Moreover, the findings accord with the theory of social exchange proposed by Blau (1964) in that when leaders exhibit ethical behaviours, team members are more likely to reciprocate them and contribute positively to team performance.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…Previous research suggests a positive relationship between ethical leaders and team performance. According to Lin et al (2019), ethical leadership can enhance team performance indirectly through leader-member exchange and capitalisation. Liu et al (2019) found that ethical leadership is positively linked to team performance through a team development competition, while the findings of Peng and Lin (2017) reveal that ethical leadership is positively related to group in-role performance.…”
Section: Influence Of Ethical Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Treviño et al (2000) and Brown et al (2005) stated that ethical leadership has two dimensions: (1) a moral personal factor, which includes integrity, fairness, concern for others and trustworthiness and (2) a moral manager factor, which includes role modelling ethical conduct, punishing, communicating and rewarding, and determining ethical standards. Mayer et al (2009) and Lin et al (2019) have therefore stated that the focus of a moral manager is more on transactional efforts that affect the ethical behaviour of employees. Khuntia and Suar (2004) posit that motivating and empowering subordinates should be vital features of ethical leadership.…”
Section: Ethical Leadership and Ethical Behaviourmentioning
confidence: 99%
“…Previous research on ethical leadership has examined its effects on various organizational outcomes, such as employee performance (Ahn et al, 2018;Lin et al, 2019;Walumbwa, et al, 2011;Zhu et al, 2015), organizational citizenship behavior (Gerpott et al, 2019;Mo and Shi, 2017), employee misconduct (Mayer, et al, 2010) and workplace bullying (Stouten, et al, 2010). However, little research has explored the theoretical relationship between ethical leadership and organizational cynicism.…”
Section: Introductionmentioning
confidence: 99%